2006
DOI: 10.1892/0891-6640(2006)20[575:eoasto]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atropine-dobutamine Stress Test on Left Ventricular Echocardiographic Parameters in Untrained Warmblood Horses

Abstract: The aim of this study was to investigate the effect of combined atropine low-dose dobutamine stress test on left ventricular parameters in adult warmblood horses, to establish a potential protocol for pharmacological stress echocardiography. Seven healthy untrained warmblood horses aged 9 to 22 years were used. Heart rate (HR) and left ventricular B- and M-mode dimensions were recorded at baseline and during stress testing with 35 microg/kg atropine IV followed by incremental dobutamine infusion of 2 to 6 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Pharmacological challenge with NBBM, a parasympatholytic agent with anticholinergic and antimuscarinic properties, caused similar echocardiographic effects as classical pharmacological stress testing, with decreased left ventricular dimensions and stroke volume and increased relative ventricular wall and interventricular septum thicknesses. 18 , 20 , 23 , 27 Cardiovascular effects of NBBM on HR and BP were visible within 2 minutes after IV administration of NBBM with a gradual reduction to baseline which occurred beyond image acquisition, similar to the findings of Morton et al, 28 who showed significant peak effects on HR and BP within 2 minutes after IV administration of NBB. Peak HR elevation occurred in the study of Morton et al 5 minutes post administration of NBB and persisted 25 minutes for DAP, MAP, and SAP and 50 minutes for HR with a gradual return to baseline.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Pharmacological challenge with NBBM, a parasympatholytic agent with anticholinergic and antimuscarinic properties, caused similar echocardiographic effects as classical pharmacological stress testing, with decreased left ventricular dimensions and stroke volume and increased relative ventricular wall and interventricular septum thicknesses. 18 , 20 , 23 , 27 Cardiovascular effects of NBBM on HR and BP were visible within 2 minutes after IV administration of NBBM with a gradual reduction to baseline which occurred beyond image acquisition, similar to the findings of Morton et al, 28 who showed significant peak effects on HR and BP within 2 minutes after IV administration of NBB. Peak HR elevation occurred in the study of Morton et al 5 minutes post administration of NBB and persisted 25 minutes for DAP, MAP, and SAP and 50 minutes for HR with a gradual return to baseline.…”
Section: Discussionsupporting
confidence: 78%
“… 11 , 12 , 13 , 14 , 15 Cardiac dimensions and function were also altered during physiological (treadmill exercise, lunging exercise) or pharmacological stress testing with atropine (parasympatholytic drug), or dobutamine (sympathomimetic drug), with high HR above 80 bpm and important increases in BP. 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 Postexercise evaluation of cardiac variables and pharmacological stress testing demonstrated decreases in left ventricular dimensions with increases in interventricular septum and left ventricular free wall thicknesses as well as an increased left ventricular fractional shortening (FS). 18 , 19 , 20 , 23 , 24 , 25 , 26 , 27 However, the influence of slight changes within the normal physiological range of HR on echocardiographic variables of cardiac function has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been achieved by manual tracking of endocardial motion and subjective evaluation of regional wall motion. 4,12,13 However, truly quantitative approaches have not been established in horses.…”
mentioning
confidence: 99%
“…To prevent the rapid heart rate decline post-exercise, pharmacological stress protocols have been developed [ 14 ]. Infusion of dobutamine provokes an increase in LV and IVS wall thickness and a decrease in LVID both in systole and diastole [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%